GENERAL ETIOLOGY OF NERVOUS ACTIVITY DISTURBANCES. NEUROGENIC PATHOLOGICAL SYNDROMES - P. F. Litvitskii (Вопросы современной педиатрии, 2013)
The most clinically significant causes and the main links of mechanisms of development of neurogenic pathological syndromes are discussed in this lecture. The article also contains tests and situational tasks for evaluation of the learning of the information, as well as reasoned variants of answers for them.